Bilateral thoracic paravertebral block for robotic hepatectomy without hepatic portal occlusion for a cirrhosis patient: a case report - Ye, Peng; Liao, Chengyu; Chen, Shi; Xue, Fushan; Zheng, Xiaochun; Wang, Danfeng (Frontiers in Oncology, 2026)
BackgroundBilateral thoracic paravertebral block (TPVB) is a regional anesthesia technique used for perioperative analgesia in thoracic and abdominal surgeries. However, its application as a key component of anesthesia to optimize surgical conditions during robotic-assisted hepatectomy, particularly in patients with severe liver cirrhosis, is not well-documented.Case presentationWe present the successful application of bilateral thoracic paravertebral block (TPVB) in conjunction with general anesthesia for robotic-assisted partial hepatectomy without hepatic portal occlusion in a 62-year-old female patient diagnosed with Child-Pugh class B liver cirrhosis. The procedure resulted in minimal intraoperative blood loss (80mL), stable hemodynamics under low central venous pressure, and an exceptionally clear surgical field, facilitating precise dissection. This procedure also markedly reduces sedative/analgesic requirements for general anesthesia and causes rapid emergence. The patient experienced effective postoperative analgesia with minimal opioid consumption and achieved early recovery milestones.ConclusionsThis case highlights the potential of bilateral TPVB to reduce hepatic sinusoidal pressure and decrease catecholamine secretion through selective visceral sympathetic nerve block. Thereby minimizing intraoperative bleeding and enhancing surgical field visualization without the need for hepatic portal occlusion. It presents a viable anesthetic strategy to optimize surgical conditions in minimally invasive hepatobiliary procedures, especially for high-risk patients with limited physiological reserve.